TRPC6 in Human Peripheral Nerves—An Investigation Using Immunohistochemistry - Cedric Raming; Carola Meier; Thomas Tschernig (NeuroSci)
Since its discovery, TRPC6 has been associated with a variety of physiological and pathophysiological processes in different tissues. It functions as a non-selective cation channel and belongs to the group of TRP channels. Its importance in the development of pain hypersensitivity is becoming increasingly apparent. This condition has already been associated with increased expression of TRPC6 in dorsal root ganglia. Apart from the fact that most of the evidence has been obtained from samples of animal origin, it remains unclear whether the channel is also expressed in peripheral nerves outside the dorsal root ganglia. The aim of this work was therefore to examine peripheral nerves from human samples for TRPC6. For this purpose, samples of both the sciatic and ulnar nerves were taken from a total of eight body donors and analyzed by immunohistochemistry. Both longitudinal and transverse sections were obtained from the samples and stained. In total, 43 of 48 histological sections showed a positive immunosignal. There were no major differences between the sciatic and ulnar nerves with regard to staining. There was a slight difference in the staining intensity of transverse and longitudinal sections. The longitudinal sections of both nerves were consistently colored slightly more intensely. However, the inter-individual differences between the donors were more pronounced. Interestingly, the samples of a donor who suffered from chronic pain syndrome during his lifetime were particularly strongly stained. This is consistent with the knowledge gained to date, largely from animal experiments, that the channel shows increased expression in pain conditions in dorsal root ganglia. In the future, TRPC6 could therefore be a target in pain therapy.